Epidemiologic link between tuberculosis and cigarette/biomass smoke exposure: Limitations despite the vast literature. Issue 4 (25th March 2015) - Bishwakarma, Raju; Kinney, William H.; Honda, Jennifer R.; Mya, Jenny; Strand, Matthew J.; Gangavelli, Avani; Bai, Xiyuan; Ordway, Diane J.; Iseman, Michael D.; Chan, Edward D.
Abstract The geographic overlap between the prevalence of cigarette smoke (CS) exposure and tuberculosis (TB) in the world is striking. In recent years, relatively large number of studies has linked cigarette or biomass fuel smoke exposure and various aspects of TB. Our goals are to summarize the significance of the known published studies, graphically represent reports that quantified the association and discuss their potential limitations. PubMed searches were performed using the key words 'tuberculosis' with 'cigarette', 'tobacco', 'smoke' or 'biomass fuel smoke.' The references of relevant articles were examined for additional pertinent papers. A large number of mostly case–control and cross‐sectional studies significantly associate both direct and second‐hand smoke exposure with tuberculous infection, active TB, and/or more severe and lethal TB. Fewer link biomass fuel smoke exposure and TB. While a number of studies interpreted the association with multivariate analysis, other confounders are often not accounted for in these analyses. It is also important to emphasize that these retrospective studies can only show an association and not any causal link. We further explored the possibility that even if CS exposure is a risk factor for TB, several mechanisms may be responsible. Numerous studies associate cigarette and biomass smoke exposure with TB but the mechanism(s) remains largely unknown. While the associative link of these two health maladies is well established, more definitive, mechanistic studies are needed to cement the effect of smoke exposure on TB pathogenesis and to utilize this knowledge in empowering public health policies.